Functional fiber spinning preparation method based on macroscopic preparation of organic micro-nano photo-thermal eutectic material
Through wet spinning technology, the electron donors and acceptors of organic near-infrared photothermal eutectic materials are grown in situ during the fiber forming process, realizing the continuous macro-preparation of organic near-infrared photothermal eutectic materials and solving the existing problems. The technology has problems of low yield and difficulty in industrial production.
Patent Information
- Application Number
- CN202411132196.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-19
- Publication Date
- 2025-01-24
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The prior art is difficult to realize the continuous macro preparation of organic micro-nano-photothermal eutectic materials, resulting in low yields and inability to industrial production.
Using wet spinning technology, by selecting fused ring small molecules with π-conjugated structure and organic conjugated small molecules with cyano, benzoquinone, and phthalic anhydride structures as electron donors and acceptors, the polymer is combined in fiber forming In-situ growth is achieved during the process, achieving continuous macro-scale preparation of organic near-infrared photothermal eutectic materials.
It has successfully overcome the difficulty of being difficult to prepare for organic micro -nano -crystals, realized the efficient macro preparation of organic near -infrared thermal compassion materials, and solved the problem of low output and industrial production difficulties.
Smart Images

Figure CN119352188A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of functional fibers, and in particular relates to a method for preparing functional fibers by spinning based on macro-scale preparation of organic micro-nano photothermal eutectic materials. Background Art
[0002] Organic photothermal materials have high photothermal conversion efficiency, and have the characteristics of tailorable molecular structure, low-temperature solution processing and adjustable physical and chemical properties. These characteristics make them of great scientific research and commercial application value in the field of low-cost, thin and flexible optoelectronic devices. However, the design of organic photothermal materials based on single-molecule systems is complex and the preparation is cumbersome, which brings challenges to practical applications (see literature: Adv.sci.2023,10,2206830). Organic eutectics can retain the properties of a single component and obtain novel optoelectronic properties due to their unique molecular arrangement and synergistic effects between multiple components (see literature: Angew.Chem.Int.Ed.2022,61,e202202571). However, the yield of organic photothermal eutectic materials with high crystallinity and regular morphology is extremely low. Currently, only milligram-level synthesis can be achieved, and industrial continuous large-scale preparation is difficult (see literature: Adv.Mater.2019,31,1902328). Therefore, it is urgent to design and develop methods for large-scale preparation of organic near-infrared photothermal eutectic materials. Summary of the invention
[0003] In order to solve the above-mentioned technical problems, this application provides the following technical solutions:
[0004] The present invention proposes a continuous, macro-quantitative preparation method and application of organic near-infrared photothermal eutectic materials. In view of the limitations of the existing technology, wet spinning is used to achieve the transformation of organic photothermal materials from micro to macro, successfully overcoming the difficulty of continuous and macro-quantitative preparation of organic micro-nano crystals.
[0005] The present invention provides a method for preparing functional fibers by spinning based on macro-scale preparation of organic micro-nano photothermal eutectic materials, comprising the following steps:
[0006] Selecting fused ring small molecules with π conjugated structure, tetrathiafulvalene and its derivatives, benzidine molecules as electron donors, organic conjugated small molecules with cyano, benzoquinone, phthalic anhydride structure as electron acceptors, accurately weighing the electron donor and acceptor at a molar ratio of 1:1 to 1:4, adding them to a suitable organic solvent and mixing them thoroughly to obtain an electron donor and acceptor stock solution with a concentration of 0.1 mmol / L to 10 mmol / L, then adding 15 to 25 wt% of polymer, treating at room temperature (25±5°C) under magnetic stirring until the polyurethane is completely dissolved, and obtaining a wet spinning solution;
[0007] Preferably, the spinning solution is subjected to wet spinning, and the wet spinning technical parameters are adjusted: the draft ratio is 1:0.1 to 1:
[0008] 10. The extrusion speed is 1-20 mL / h, the pinhole diameter is 14-20 G, and the coagulation bath temperature is 5-50 °C. The confined self-assembly and large-scale preparation of organic photothermal eutectic materials in the fiber forming process are realized, and a new type of thermal storage fiber based on organic photothermal eutectic materials is constructed.
[0009] Preferably, the electron donor of the present invention is selected from N,N-dimethyl-2-naphthylamine, naphthalene, benzo[c]phenanthrene, benzo[a]phenanthrene, phenanthrene, coronene, triphenylene, benzo(a)anthracene, 7,12-dimethylbenzo[a]anthracene, anthracene, 1,12-benzoperylene, perylene, dibenzo(a,h)pyrene, benzo[E]pyrene, benzo[a]pyrene, pyrene, dibenzothiophene, benzo[1,2-b:4,5-bˋ]diphenylene, 1,12-benzoperylene, 1,12-benzoperylene, 1,12-benzoperylene, 1,12-benzoperylene, 1,12-benzoperylene, 1,12-benzoperylene, 1,12-benzothiophene ... Thiophene, benzonaphthyl (1,2-D) thiazole, tetrathiafulvalene, thiafulvalene benzoic acid, tetrathiafulvalene tetrabenzaldehyde, dibenzotetrathiafulvalene, benzidine, 3,3',5,5'-tetramethylbenzidine, N,N,N",N'-tetramethylbenzidine, 4,4'-diiodo-3,3'-dimethylbiphenyl, 3,3'-diaminobenzidine or 4,4'-diamino-3,3'-dimethylbiphenyl.
[0010] Preferably, the electron acceptor of the present invention is selected from o-tetrachlorobenzoquinone, tetrachlorobenzoquinone, tetrafluoro-p-benzoquinone, tetrabromo-p-benzoquinone, tetraiodobenzoquinone, 1,2,4,5-tetracyanobenzene, 7,7,8,8-tetracyanobenzoquinodimethane, 2-fluoro-7,7,8,8-tetracyanoquinodimethane, 2,3,5,6-tetrafluoro-7,7',8,8'-tetracyanodimethyl-p-benzoquinone, 2,5-difluoro-7,7,8,8-tetracyanobenzoquinodimethane, 2,3,5,6-tetrafluoroterephthalonitrile, tetrachloroisophthalonitrile, 4,5-dichlorophthalonitrile, 3,4,5,6-tetrafluorophthalonitrile, phthalic anhydride, tetrabromophthalic anhydride, 3,4,5,6-tetrafluorophthalic anhydride or tetrachlorophthalic anhydride.
[0011] Preferably, the organic solvent is one of dimethyl sulfoxide, N,N-dimethylformamide, acetonitrile, dichloromethane, tetrahydrofuran and chloroform, or a mixed solution thereof.
[0012] Preferably, in the spinning solution, the polymer is selected from one of polyester polyurethane, polyether polyurethane, thermoplastic polyurethane, water-based polyurethane, nylon, acrylic fiber, cellulose acetate and nylon, or a mixture thereof.
[0013] Preferably, in the macro-preparation method, the coagulation bath is selected from water, alcohols, acetonitrile, or a mixed solvent thereof.
[0014] Preferably, the coagulation bath further contains an acidic or alkaline additive.
[0015] Furthermore, the acidic additive used in the coagulation bath of the present invention is a mixture of one or more of sulfuric acid, sodium sulfate and hydrochloric acid.
[0016] Furthermore, the alkaline additive used in the coagulation bath of the present invention is a mixture of one or more of sodium hydroxide, potassium hydroxide and ammonia water.
[0017] The present invention selects fused ring small molecules with π-conjugated molecular structure, tetrathiafulvalene and its derivatives, and benzidine molecules as electron donors from the aspects of molecular structure and energy level matching, and uses organic conjugated small molecules with structures such as cyano, benzoquinone, and phthalic anhydride as electron acceptors, and realizes the in-situ growth and continuous preparation of organic near-infrared photothermal eutectic materials through spinning chemical strategies. In the process of wet spinning, when the polyurethane base material contacts the water in the coagulation bath, it crosslinks to form fibers. At the same time, the donor and acceptor raw materials grow in-situ on the surface and inside of the fiber under the driving force of charge transfer to form organic micro-nano eutectic materials. As the fiber is continuously formed and collected by the fiber collector, the organic micro-nano eutectic material is also continuously prepared and produced.
[0018] The technical solution of the present invention has the following advantages over the prior art:
[0019] (1) The present invention is based on eutectic engineering, adopts organic donor and acceptor materials, and prepares organic near-infrared photothermal eutectic materials in situ inside and on the surface of polyurethane fibers through a wet spinning process, thus avoiding cumbersome and complicated molecular design and synthesis processes.
[0020] (2) The present invention provides a continuous and large-scale preparation method of organic near-infrared photothermal eutectic materials, which overcomes the difficulties of low yield and inability to industrialize organic micro-nano eutectics. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 It is a set of molecular formulas of the electron donors described in the claims of the present invention.
[0022] Figure 2 It is a set of molecular formulas of the electron acceptors described in the claims of the present invention.
[0023] Figure 3 Actual picture (a) and SEM picture (b) of the NDA-CA loaded organic photothermal eutectic fiber provided in Example 1 of the present invention.
[0024] Figure 4 This is a SEM image of the photothermal eutectic material NDA-CA loaded on the fiber provided in Example 1 of the present invention.
[0025] Figure 5This is the UV-visible-near-infrared absorption spectra of the polyurethane, NDA-CA cocrystal and NDA-CA@polyurethane provided in Example 1 of the present invention.
[0026] Figure 6 The power density provided in Example 1 of the present invention is 0.301 W / cm 2 Photothermal performance test diagram of polyurethane, NDA-CA eutectic and NDA-CA@polyurethane.
[0027] Figure 7 The NDA-CA eutectic provided in Example 1 of the present invention is at 0.301W / cm 2 Photothermal stability test diagram (a) and NDA-CA@polyurethane at 0.301W / cm 2 Photothermal stability test diagram (b). DETAILED DESCRIPTION
[0028] The present invention is further described below in conjunction with the drawings and specific embodiments so that those skilled in the art can better understand the present invention and implement it, but the embodiments are not intended to limit the present invention.
[0029] Example 1
[0030] 0.085 g of N,N-dimethyl-2-naphthylamine (NDA) and 0.125 g of o-tetrachlorobenzoquinone (CA) were added to 9 mL of a mixed solvent of N,N-dimethylformamide and acetonitrile (volume ratio of 6:3), and then 1.25 g of polyurethane (PU) was added, and magnetic stirring was performed until PU was completely dissolved to obtain a spinning solution.
[0031] The spinning solution was sucked into a disposable syringe and fixed on a propulsion pump for wet spinning. The needle size was 18G, the propulsion speed was 6mL / h, the draft ratio was 1:1.5, the temperature was 20°C, and the humidity was 45%. The polyurethane fiber (NDA-CA@PU) loaded with NDA-CA eutectic material was solidified in a deionized water coagulation bath.
[0032] The NDA-CA@PU fiber was further ultrasonically stripped to obtain pure NDA-CA organic micro-nano crystal material. The steps are as follows: 300 mL of deionized water was added to a beaker, and 10 g of fiber loaded with NDA-CA organic micro-nano crystal material was completely immersed in it, and the NDA-CA organic micro-nano crystal grown on the fiber was stripped under ultrasonic conditions of 20°C and 25kHz; after ultrasonic treatment for 1 hour, the supernatant was removed and the precipitate was dried at 7000r / min to obtain pure NDA-CA organic micro-nano crystal material.
[0033] Example 2
[0034] 0.085 g of N,N-dimethyl-2-naphthylamine (NDA) and 0.125 g of o-tetrachlorobenzoquinone (CA) were added to 8 mL of a mixed solvent of N,N-dimethylformamide and acetonitrile (volume ratio of 5:3), and then 1.2 g of polyurethane (PU) was added, and magnetic stirring was performed until PU was completely dissolved to obtain a spinning solution.
[0035] The spinning solution was sucked into a disposable syringe and fixed on a propulsion pump for wet spinning. The needle size was 18G, the propulsion speed was 3mL / h, the draft ratio was 1:5, the temperature was 25°C, and the humidity was 45%. The polyurethane fiber (NDA-CA@PU) loaded with NDA-CA eutectic material was solidified in a deionized water coagulation bath.
[0036] The NDA-CA@PU fiber was further ultrasonically stripped to obtain pure NDA-CA organic micro-nano crystal material. The steps are as follows: 300 mL of deionized water was added to a beaker, and 10 g of fiber loaded with NDA-CA organic micro-nano crystal material was completely immersed in it, and the NDA-CA organic micro-nano crystal grown on the fiber was stripped under ultrasonic conditions of 20°C and 25kHz; after ultrasonic treatment for 1 hour, the supernatant was removed and the precipitate was dried at 7000r / min to obtain pure NDA-CA organic micro-nano crystal material.
[0037] Example 3
[0038] 0.085 g of N,N-dimethyl-2-naphthylamine (NDA) and 0.125 g of o-tetrachlorobenzoquinone (CA) were added to 9 mL of a mixed solvent of N,N-dimethylformamide and acetonitrile (volume ratio of 6:3), and then 1.25 g of polyurethane (PU) was added, and magnetic stirring was performed until PU was completely dissolved to obtain a spinning solution.
[0039] The spinning solution was sucked into a disposable syringe and fixed on a propulsion pump for wet spinning. The needle size was 18G, the propulsion speed was 15mL / h, the draft ratio was 1:3, the temperature was 15°C, and the humidity was 40%. The polyurethane fiber (NDA-CA@TPU) loaded with NDA-CA eutectic material was solidified in a deionized water coagulation bath.
[0040] The NDA-CA@PU fiber was further ultrasonically stripped to obtain pure NDA-CA organic micro-nano crystal material. The steps are as follows: 300 mL of deionized water was added to a beaker, and 15 g of fiber loaded with NDA-CA organic micro-nano crystal material was completely immersed in it, and the NDA-CA organic micro-nano crystal grown on the fiber was stripped under ultrasonic conditions of 25°C and 25kHz; after ultrasonic treatment for 1 hour, the supernatant was removed and the precipitate was dried at 6500r / min to obtain pure NDA-CA organic micro-nano crystal material.
[0041] Example 4
[0042] 0.085 g of N,N-dimethyl-2-naphthylamine (NDA) and 0.125 g of o-tetrachlorobenzoquinone (CA) were added to 8 mL of a mixed solvent of N,N-dimethylformamide and acetonitrile (volume ratio of 5:3), and then 1.2 g of polyurethane (PU) was added, and magnetic stirring was performed until PU was completely dissolved to obtain a spinning solution.
[0043] The spinning solution was sucked into a disposable syringe and fixed on a propulsion pump for wet spinning. The needle size was 18G, the propulsion speed was 10mL / h, the draft ratio was 1:2, the temperature was 20°C, and the humidity was 40%. The polyurethane fiber (NDA-CA@PU) loaded with NDA-CA eutectic material was solidified in a deionized water coagulation bath.
[0044] The NDA-CA@PU fiber was further ultrasonically stripped to obtain pure NDA-CA organic micro-nano crystal material. The steps are as follows: 300 mL of deionized water was added to a beaker, and 15 g of fiber loaded with NDA-CA organic micro-nano crystal material was completely immersed in it, and the NDA-CA organic micro-nano crystal grown on the fiber was stripped under ultrasonic conditions of 25°C and 25kHz; after ultrasonic treatment for 1 hour, the supernatant was removed and the precipitate was dried at 7000r / min to obtain pure NDA-CA organic micro-nano crystal material.
[0045] Example 5
[0046] 0.085 g of N,N-dimethyl-2-naphthylamine (NDA) and 0.125 g of o-tetrachlorobenzoquinone (CA) were added to 7 mL of a mixed solvent of N,N-dimethylformamide and acetonitrile (volume ratio of 4:3), and then 1.25 g of polyurethane (PU) was added, and magnetic stirring was performed until PU was completely dissolved to obtain a spinning solution.
[0047] The spinning solution was sucked into a disposable syringe and fixed on a propulsion pump for wet spinning. The needle size was 18G, the propulsion speed was 20mL / h, the draft ratio was 1:1, the temperature was 25°C, and the humidity was 45%. The polyurethane fiber (NDA-CA@PU) loaded with NDA-CA eutectic material was solidified in a deionized water coagulation bath.
[0048] The NDA-CA@PU fiber was further ultrasonically stripped to obtain pure NDA-CA organic micro-nano crystal material. The steps are as follows: 300 mL of deionized water was added to a beaker, and 10 g of fiber loaded with NDA-CA organic micro-nano crystal material was completely immersed in it, and the NDA-CA organic micro-nano crystal grown on the fiber was stripped under ultrasonic conditions of 25°C and 25kHz; after ultrasonic treatment for 1 hour, the supernatant was removed and the precipitate was dried at 7000r / min to obtain pure NDA-CA organic micro-nano crystal material.
[0049] Effect evaluation 1
[0050] See also Figure 1 , which is the molecular formula set of the electron donor described in the claims of the present invention, is a fused ring small molecule with a π-conjugated structure, tetrathiafulvalene and its derivatives, and benzidine molecules.
[0051] See also Figure 2 , which is a molecular formula set of the electron acceptor described in the claims of the present invention, is an organic conjugated small molecule with structures such as cyano, benzoquinone, and phthalic anhydride.
[0052] See also Figure 3 , (a) is a real shot of the polyurethane fiber (NDA-CA@PU) loaded with NDA-CA eutectic material obtained by wet spinning provided in Example 1; (b) is a SEM picture of the NDA-CA@PU fiber, which shows that the fiber is uniform in thickness and has a diameter of ~400μm.
[0053] See also Figure 4 , is a SEM image of NDA-CA organic micro-nano crystals loaded on fibers provided in Example 1 of the present invention; Figure 4 It can be seen that the crystals are located on the surface and inside of the fiber, are evenly distributed, and have a length of 5 to 20 μm, proving that NDA-CA organic micro-nano crystals can be successfully prepared in large quantities through wet spinning technology.
[0054] See also Figure 5 , which is the UV-Vis-NIR absorption spectra of the polyurethane, NDA-CA eutectic and NDA-CA@polyurethane provided in Example 1 of the present invention; compared with the pure polyurethane fiber, the absorption of NDA-CA eutectic and NDA-CA@polyurethane fiber has undergone red shift and has reached the near-infrared region.
[0055] See also Figure 6 , which is a comparison of the photothermal performance of polyurethane, NDA-CA eutectic and NDA-CA@polyurethane fiber provided in Example 1 of the present invention. 2Under the irradiation of 808nm laser light, the temperatures of polyurethane, NDA-CA@polyurethane fiber and NDA-CA eutectic material can rise from room temperature to 27.8℃, 78℃ and 93℃ respectively, which fully demonstrates the excellent photothermal properties of the NDA-CA eutectic material prepared by the present invention.
[0056] See also Figure 7 , the NDA-CA eutectic provided in Example 1 of the present invention is at 0.301W / cm 2 Photothermal stability test diagram (a) and NDA-CA@polyurethane at 0.301W / cm 2 The photothermal stability test diagram (b) shows that the NDA-CA eutectic and NDA-CA@polyurethane fiber have excellent photothermal performance and photothermal stability through 12 heating and cooling cycle tests at the same power density, proving the successful large-scale preparation of organic photothermal eutectic materials based on wet spinning technology.
[0057] Obviously, the above embodiments are merely examples for clear explanation and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the protection scope of the invention.
Claims
1. A method for preparing functional fibers by spinning based on macro-scale preparation of organic micro-nano photothermal eutectic materials, characterized in that: The steps include: S1: Selecting fused ring small molecules with π conjugated structure, tetrathiafulvalene and its derivatives or benzidine molecules as electron donors, and organic conjugated small molecules with cyano, benzoquinone or phthalic anhydride structure as electron acceptors, weighing the electron donor and the electron acceptor in a molar ratio of 1:1-4, adding them into an organic solvent and mixing them thoroughly to obtain a 0.1mmol / L-10mmol / L electron donor and acceptor stock solution, then adding a polymer with a concentration of 15-25wt%, treating at room temperature and magnetic stirring until the polymer is completely dissolved, and obtaining a wet spinning solution; S2: Wet-spinning the wet spinning solution, and adjusting the wet spinning technical parameters: draft ratio 1: 0.1-10, extrusion speed 1-20mL / h, pinhole aperture 14-20G, coagulation bath temperature 5-50°C, to achieve confined self-assembly and macro-scale preparation of the organic photothermal eutectic material in the fiber forming process, and prepare the functional fiber spinning based on the macro-scale preparation of the organic micro-nano photothermal eutectic material.
2. The preparation method according to claim 1, characterized in that The electron donor is selected from N,N-dimethyl-2-naphthylamine, naphthalene, benzo[c]phenanthrene, benzo[a]phenanthrene, phenanthrene, coronene, triphenylene, benzo(a)anthracene, 7,12-dimethylbenzo[a]anthracene, Anthracene, 1,12-benzoperylene, perylene, dibenzo(a,h)pyrene, benzo[E]pyrene, benzo[a]pyrene, pyrene, dibenzothiophene, benzo[1,2-b:4,5-bˋ]dithiophene, benzonaphthalene(1,2-D)thiazole, tetrathiafulvalene, thiafulvalene benzoic acid, tetrathiafulvalene tetrabenzaldehyde, dibenzotetrathiafulvalene, benzidine, 3,3',5,5'-tetramethylbenzidine, N,N,N",N'-tetramethylbenzidine, 4,4'-diiodo-3,3'-dimethylbiphenyl, 3,3'-diaminobenzidine or 4,4'-diamino-3,3'-dimethylbiphenyl.
3. The preparation method according to claim 1, characterized in that: The electron acceptor is selected from o-tetrachlorobenzoquinone, tetrachlorobenzoquinone, tetrafluoro-p-benzoquinone, tetrabromo-p-benzoquinone, tetraiodobenzoquinone, 1,2,4,5-tetracyanobenzene, 7,7,8,8-tetracyanobenzoquinodimethane, 2-fluoro-7,7,8,8-tetracyanoquinodimethane, 2,3,5,6-tetrafluoro-7,7',8,8'-tetracyanodimethyl-p-benzoquinone, 2,5-difluoro-7,7,8,8-tetracyanobenzoquinodimethane, 2,3,5,6-tetrafluoroterephthalonitrile, tetrachloroisophthalonitrile, 4,5-dichlorophthalonitrile, 3,4,5,6-tetrafluorophthalonitrile, phthalic anhydride, tetrabromophthalic anhydride, 3,4,5,6-tetrafluorophthalic anhydride or tetrachlorophthalic anhydride.
4. The preparation method according to claim 1, characterized in that: The organic solvent is one or more of dimethyl sulfoxide, N,N-dimethylformamide, acetonitrile, dichloromethane, tetrahydrofuran and chloroform.
5. The preparation method according to claim 1, characterized in that: In the wet spinning solution, the polymer is selected from one or more of polyester polyurethane, polyether polyurethane, thermoplastic polyurethane, waterborne polyurethane, nylon, acrylic fiber, cellulose acetate and nylon.
6. The preparation method according to claim 1, characterized in that: The coagulation bath is selected from one of water, alcohols and acetonitrile or a mixed solvent thereof.
7. The preparation method according to claim 1, characterized in that: The coagulation bath further contains an acidic additive or an alkaline additive.
8. The preparation method according to claim 7, characterized in that: The acidic additive is selected from one or more mixtures of sulfuric acid, sodium sulfate and hydrochloric acid.
9. The preparation method according to claim 7, characterized in that: The alkaline additive is selected from one or more mixtures of sodium hydroxide, potassium hydroxide and ammonia water.